(untitled) (Boletín de la Sociedad Zoológica del Uruguay, 2024)
Tityus bahiensis does not present severe records of scorpionism in Argentina, it does in Brazil. In Argentina, T. bahiensis is found in Corrientes, Misiones, Chaco, Entre Ríos, Buenos Aires and Santa Fe provinces, with some records along the Paraná and Uruguay rivers. In this contribution, we report a living specimen from the City of San Rafael, Mendoza.